Functionalization of TiO2 inverse opal structure with atomic layer deposition grown Cu for photocatalytic and antibacterial applications - Pham Khai; Ali-Löytty Harri; Saari Jesse; Zubair Muhammad; Valden Mika; Lahtonen Kimmo; Kinnunen Niko; Gunell Marianne; Saarinen Jarkko J (Elsevier, 2022)
TiO2 inverse opal (IO) structure surfaces were functionalized with a sub-monolayer amount of Cu by atomic layer deposition (ALD) and tested for photocatalytic and antimicrobial applications. Decomposition of acetylene (C2H2) into CO2 and reduction of CO2 into CH4 were tested in the gas phase and photodegradation of methylene blue (MB) was tested in the liquid phase. Antimicrobial activity was tested against Gram-positive Staphylococcus aureus (S. aureus) bacteria. ALD Cu without any post-deposition heat treatment (HT) decreased the photo degradation rate of both C2H2 and MB but improved the activity towards CO2 reduction. ALD Cu increased MB photodegradation rate and antimicrobial activity only after HT at 550 C, which was linked to the improved chemical stability Cu after the HT. The same HT decreased the activity towards CO2 reduction and decomposition of C2H2. The HT induced desorption of loosely bound ALD Cu+/2+ from the TiO2 IO surface and the remaining Cu+/2+ was reduced to Cu+. The photocatalytic and antimicrobial activity of TiO2 IO can be tailored by the addition of a sub-monolayer amounts of Cu with performance depending on the targeted reaction.